2021
DOI: 10.3390/ijms221910494
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of the Aux/IAA and Auxin Response Factor Gene Family in Medicago truncatula

Abstract: Aux/IAA and auxin response transcription factor (ARF) genes are key regulators of auxin responses in plants. A total of 25 MtIAA and 40 MtARF genes were identified based on the latest updated Medicago truncatula reference genome sequence. They were clustered into 10 and 8 major groups, respectively. The homologs among M. truncatula, soybean, and Arabidopsis thaliana shared close relationships based on phylogenetic analysis. Gene structure analysis revealed that MtIAA and MtARF genes contained one to four conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…Several studies have indicated that promoters influence the temporal and spatial expression of genes, and cis-elements within promoters are key to regulating gene function through interplay with trans-acting factors [ 33 ]. Multiple Aux/IAA genes with promoter elements associated with abiotic stress and hormones have been found to participate in these abiotic stress responses [ 34 ]. For example, OsIAA20 and most of the MtIAA genes exhibited wide-ranging responses to salt stress, and more than half of the FveIAA genes responded to IAA treatment [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that promoters influence the temporal and spatial expression of genes, and cis-elements within promoters are key to regulating gene function through interplay with trans-acting factors [ 33 ]. Multiple Aux/IAA genes with promoter elements associated with abiotic stress and hormones have been found to participate in these abiotic stress responses [ 34 ]. For example, OsIAA20 and most of the MtIAA genes exhibited wide-ranging responses to salt stress, and more than half of the FveIAA genes responded to IAA treatment [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the interaction between MoIAAs and MoARFs was complex; some MoIAA proteins may interact with several MoARFs and vice versa, representing functional redundancy within the Aux/IAA proteins [ 38 ]. For example, MtIAA12 and MtIAA21 interacted with MtARF29, which also interacts with most of the MtARFs [ 34 ]. Notably, MoIAA3 and MoIAA13 proteins were at the center of the network, suggesting that they interact strongly with other proteins, while MoARF2.1 and MoARF17 exhibit the least interaction with others.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, phylogenetic analysis of these TIR1/AFB auxin receptors found in the G. max genome have not yet been explored. We identified 61 Aux/IAA genes in G. max , which largely followed the clade structure of previous analyses (Remington et al ., 2004; Liu et al ., 2021; Ali et al ., 2022). Similarly, we identified 55 ARFs in the G. max genome which fell into orthology groups largely as expected based on previous analyses (Le et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…AtARF8 and AtARF6 also play an essential role in cambium establishment and maintenance (Ben-Targem et al, 2021). In M. truncatula , the ARF8 ortholog exhibits slightly elevated expression in the petiole and stem, but not the leaf (Liu et al, 2021). Similarly, our analysis found a slight association of GmARF8_C.1 with hypocotyl, leaf and cotyledon tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation